Protein scaffolded DNA tetrads enable efficient delivery and ultrasensitive imaging of miRNA through crosslinking hybridization chain reaction. Issue 21 (14th May 2018) - Huang, Du-Juan; Huang, Zhi-Mei; Xiao, Hu-Yan; Wu, Zhen-Kun; Tang, Li-Juan; Jiang, Jian-Hui
Abstract : DNA tetrads as an integrated platform that enables realization of efficient DNA delivery and HCR amplification in situ on nanostructures. Abstract : Efficient intracellular delivery of nucleic acids to achieve sensitive detection and gene regulation is essential for chemistry and biology. Here we developed a novel protein scaffolded DNA tetrad, a four-arm DNA nanostructure constructed using streptavidin (SA) protein and four biotinylated hairpin DNA probes for efficient nucleic acid delivery and ultrasensitive miRNA imaging through crosslinking hybridization chain reaction (cHCR). DNA tetrads were easy to prepare and allowed precise control of the structure of the probes. DNA tetrads showed rapid intracellular delivery of DNA probes and high efficiency in lysosome escape by using confocal images for individual cells and flow cytometry for a large population of cells. cHCR allowed generating clumps of crosslinked hydrogel networks specifically to target miRNA, affording high sensitivity and spatial resolution for imaging. To our knowledge, this is the first time that HCR amplification has been realized in situ on nanostructures. Moreover, the FRET based design of cHCR conferred improved precision with the use of dual-emission ratiometric imaging to avoid false signals in biological systems. Intracellular imaging experiments further showed that DNA tetrad based cHCR could realize ultrasensitive and accurate miRNA imaging in living cells. Moreover, DNA tetrad based cHCR provided a potential tool for quantitative measurement of intracellular miRNA. The results suggested that this developed strategy provided a useful platform for nucleic acid delivery and low level biomarker imaging.